Tropical cyclones of the North Atlantic Ocean, 1851-2006 : with 2007 and 2008 track maps included - Blake, Eric S; David, Joan E; Neumann, Charles J; Landsea, Chris; McAdie, Colin; United States. National Environmental Satellite, Data, and Information Service; National Hurricane Center (1965-1995); National Climatic Data Center (U.S.) (Asheville, N.C. : U.S. Dept. of Commerce, National Oceanic and Atmospheric Administration, National Weather Service, National Environmental Satellite, Data, and Information Service, 2009)
"Includes 2007 & 2008 track maps"--Cover "Original publication - June, 1978." Includes bibliographical references (p. 37-43) Mode of access: Internet. U. S. Depository Item